Formulation and evaluation of hand sanitizer gel containing infused of binahong leaf (Anredera cordifolia) as antibacterial preparation - Rahmasari, Dyah; Hendradi, Esti; Chasanah, Uswatun (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2020)
Hand sanitizer gel is one of the alternative methods for hand hygiene when soap and water are not available. Binahong leaf (Anredera cordifolia) is a natural herb that has phenolic, flavonoids, saponins, and the steroid-terpenoids compound, which is potentially used as the active ingredient in the hand sanitizer gel. The primary purpose of this research was to determine the antibacterial potential and physicochemical properties of a hand-sanitizer gel containing binahong leaves’ infusion against Staphylococcus aureus. The efficacy of this formulation was tested against a bacterial strain using the disc diffusion method and determined by measuring the inhibition zone of each preparation. The testing of physicochemical properties includes the organoleptic test, pH, viscosity, and gel spreadability. The physicochemical characteristics of the gel showed excellent properties for all formulas. The antibacterial test showed that hand sanitizer gel containing an infusion of binahong’s leaves has an inhibition zone (6.02 mm; 6.24 mm; 6.55 mm), almost close to a positive control (9.15 mm). In conclusion, the formulated hand sanitizer gel possesses the antibacterial potential to inhibit S. aureus.